Functional Background Identity, Diversity, and Individual Performance in Cross-Functional Teams - Randel, Amy E.; Jaussi, Kimberly S. (Academy of Management Journal, 2003)
This study's examination of demography, personal, and social identity related to functional background offers insights about individuals' performance in cross-functional teams. We considered both the interaction between identity and dissimilarity with other team members and the interaction between identity and membership in a team's minority or majority. In explaining the relationship between identity and an individual's performance as a cross-functional team member, minority/majority membership interacted significantly with identity, but actual degree of dissimilarity did not.